TUJUAN NEGARA PESPEKTIF MAQOSHID SYARIAH Al-SYATIBI DAN IBNU ASYUR - Amir Hamzah; Sabrina Nikmatul Khoiriyah (Wasīlah: Journal Of Sharia Sciences, 2026)
This study discusses the objectives of the state from the perspective of the maqoshid sharia of A-Syatibi and Ibn Asyur with the aim of knowing the objectives of the state in the perspective of the two figures. This study uses a literature review approach where data is obtained from sources of books, and articles that discuss the thoughts of As-Syatibi and Ibn Asyur as well as documents related to this study. The results of this study show that between the thoughts of Al-Syatibi and Ibn Asyur basically have differences regarding the maqoshid sharia itself, so from this difference the objectives of the state in their perspectives are also different, Ay-Syatibi emphasizes the objectives of the formation of the state on five points, namely protecting religion, soul, aka, family, and property while Ibn Asyur emphasizes the objectives of the state on broader points such as equality, tolerance to getting jobs that are in accordance with the fields of each citizen. The conclusion in this study shows that As-Syatibi and Ibn Asyur, although they both discuss the maqoshid of sharia, have different perspectives, so with this background, their thoughts also have differences in the goals of the state.